2009
DOI: 10.1038/emboj.2009.239
|View full text |Cite
|
Sign up to set email alerts
|

FoxM1, a critical regulator of oxidative stress during oncogenesis

Abstract: The transcription factor FoxM1 is over-expressed in most human malignancies. Although it is evident that FoxM1 has critical functions in tumour development and progression, the mechanisms by which FoxM1 participates in those processes are not understood. Here, we describe an essential role of FoxM1 in the regulation of oxidative stress that contributes to malignant transformation and tumour cell survival. We identify a negative feedback loop involving FoxM1 that regulates reactive oxygen species (ROS) in proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
214
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(231 citation statements)
references
References 47 publications
17
214
0
Order By: Relevance
“…FoxM1 has been shown to activate the oncogenic pathways that are important in carcinogenesis such as mitogen activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK), phosphatdyl inositol 3-kinase (PI3k)/Akt), nuclear factor kappa-B and sonic hedgehog (SHH) [33][34][35][36][37]. Moreover, FoxM1 has been shown to decrease the gene expression levels of the tumor suppressor genes and also the genes involved in cellular senescence like p53 and p21 cip1 [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…FoxM1 has been shown to activate the oncogenic pathways that are important in carcinogenesis such as mitogen activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK), phosphatdyl inositol 3-kinase (PI3k)/Akt), nuclear factor kappa-B and sonic hedgehog (SHH) [33][34][35][36][37]. Moreover, FoxM1 has been shown to decrease the gene expression levels of the tumor suppressor genes and also the genes involved in cellular senescence like p53 and p21 cip1 [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this transcription factor appears to play a major role in early tumorigenesis of head and neck squamous cell cancers (Gemenetzidis et al, 2009) and seems not to induce apoptosis (Kalinina et al, 2003;Gusarova et al, 2007;Park et al, 2009). It displays a proliferation-specific expression pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a forkhead/wingedhelix transcription factor that regulates malignant growth and invasion (Wierstra and Alves, 2007). However, it does not induce apoptosis (Kalinina et al, 2003;Gusarova et al, 2007;Park et al, 2009) (Figure 5e) that was more pronounced in ras-transformed cells and could be abolished by incubating ras-and MKK3 act -transformed cells with the p38 inhibitor SB203580 (Figure 5f). Thus, FOXM1 should be considered downstream of the Ha-Ras-MKK3-p38 cascade.…”
Section: Foxm1 Expression Is Upregulated In Ha-ras and Mkk3 Act -Nih3mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have implicated FoxM1 in tumorigenesis, as it is overexpressed in various human cancers including lung cancer (24)(25)(26)(27)(28). Wang and colleagues showed that proliferation of lung tumor cells was diminished in Mx-Cre FoxM1 À/À mouse mutants and that these mice had a significant reduction in the number and size of lung adenomas (28).…”
Section: Introductionmentioning
confidence: 99%